Pengaruh Kualitas Pelayanan Dan Harga Terhadap Keputusan Pembelian Pada Alfamart Cabang Darmawangsa Kabupaten Bekasi - Apriyani, Intan; Akbar, Muhammad (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study is motivated by a decrease of around 80% in February 2024 due to service quality andprice at Alfamart Darmawangsa. This study aims to determine the effect of service quality andprice on purchasing decisions for customers of Alfamart Darmawangsa Branch, Bekasi Regency.The type of data in this study is a quantitative approach. This study uses 2 independent variables,namely service quality and price on the dependent variable of purchasing decisions. In this studythe sample used was 150 customers at Alfamart Darmawangsa. The data was processed usingSPSS 25 with the t test, f test, multiple linear regression, and the coefficient of determination. Theresults showed that there is a partially significant influence between Service Quality onPurchasing Decisions at Alfamart in Darmawangsa branch Where t count 32.157> t table 1.976and a significant value of 0.000 <0.05. There is a partially significant influence between Price onPurchasing Decisions at Alfamart in Darmawangsa branch Where t count 30.949> t table 1.976and a significant value of 0.000 <0.05. There is a simultaneous significant influence betweenService Quality and Price on Purchasing Decisions at Alfamart Darmawangsa branch, BekasiRegency where the F value is F count 712.581> t table 3.06. The contribution made by ServiceQuality and Price simultaneously to Purchasing Decisions is 90.6%, while the remaining 9.4% isinfluenced by other factors not included in this study.